2005
DOI: 10.1002/rcm.2040
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low volume plasma sample precipitation procedure for liquid chromatography/tandem mass spectrometry assays used for drug discovery applications

Abstract: The demand for high sensitivity bioanalytical methods has dramatically increased in the drug discovery stage; in addition, there has been a growing trend of reducing the sample volume that is required for these assays. A sensitive high-performance liquid chromatography/tandem mass spectrometry (HPLC/MS/MS) procedure has been developed and tested to meet these needs. The assay requires only a low plasma sample volume (10 microL) and employs a protein precipitation procedure using a 1:6 plasma/acetonitrile ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…MeOH, EtOH and CH 3 CN) can be effective in removing plasma proteins at a P‐P ratio of 2:1 (v/v),23 Xu et al . reported that lowering the plasma sample volume and increasing the P‐P ratio (6:1, v/v) resulted in a significant reduced level of noise background for analytes and an evidently lower limit of detection, as compared to results obtained using a procedure with a lower P‐P ratio (3:1, v/v) 24. In this study, we found that using an increased P‐P ratio (4:1, v/v; relative to our conventionally used P‐P ratio 2:1, v/v) also reduced the matrix effect window.…”
Section: Resultsmentioning
confidence: 99%
“…MeOH, EtOH and CH 3 CN) can be effective in removing plasma proteins at a P‐P ratio of 2:1 (v/v),23 Xu et al . reported that lowering the plasma sample volume and increasing the P‐P ratio (6:1, v/v) resulted in a significant reduced level of noise background for analytes and an evidently lower limit of detection, as compared to results obtained using a procedure with a lower P‐P ratio (3:1, v/v) 24. In this study, we found that using an increased P‐P ratio (4:1, v/v; relative to our conventionally used P‐P ratio 2:1, v/v) also reduced the matrix effect window.…”
Section: Resultsmentioning
confidence: 99%
“…The automation of front-end sample preparation with microplate technology prior to HPLC-MS/MS analyses has played a key role in the high-throughput bioanalytical process [54,109,[121][122][123][124][125]. A microplate is a flat plate composing of multiple sample vials (known as "wells") arranged in rows.…”
Section: Microplate Techniquesmentioning
confidence: 99%
“…In the past, this has been time consuming, and DMPK labs are evaluating new automation techniques and generic LC/MS methods to keep turnaround in pace with requests [1][2][3][4][5]. Low molecular weight, polar compounds may be important in drug discovery because of the good physical properties they possess, including bioavailability [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%